Non-nucleotide Agonists Triggering P2X7 Receptor Activation and Pore Formation - Di Virgilio, Francesco; Giuliani, Anna L.; Vultaggio-Poma, Valentina; Falzoni, Simonetta; Sarti, Alba C. (Frontiers in Pharmacology, 2018)
The P2X7 receptor (P2X7R) is a ligand-gated plasma membrane ion channel belonging to the P2X receptor subfamily activated by extracellular nucleotides. General consensus holds that the physiological (and maybe the only) agonist is ATP. However, scattered evidence generated over the last several years suggests that ATP might not be the only agonist, especially at inflammatory sites. Solid data show that NAD+ covalently modifies the P2X7R of mouse T lymphocytes, thus lowering the ATP threshold for activation. Other structurally-unrelated agents have been reported to activate the P2X7R via a poorly understood mechanism of action: a) the antibiotic polymixin B, possibly a positive allosteric P2X7R modulator, b) the bactericidal peptide LL-37, c) the amyloidogenic β peptide, and d) serum amyloid A. Some agents, such as Alu-RNA, have been suggested to activate the P2X7R acting on the intracellular N- or C-terminal domains. Mode of P2X7R activation by these non-nucleotide ligands is as yet unknown, however these observations raise the intriguing question of how these different non-nucleotide ligands may co-operate with ATP at inflammatory or tumor sites. New information obtained from the cloning and characterization of the P2X7R from exotic mammalian species (e.g. giant panda) and data from recent patch-clamp studies are strongly accelerating our understanding of P2X7R mode of operation, and may provide hints to the mechanism of activation of P2X7R by non-nucleotide ligands.